The Role of Attorney Speech and Advocacy in the Subversion and Protection of Constitutional Governance - Margaret Tarkington (Washington University Journal of Law and Policy, 2022)
Attorneys who advised and assisted in Trump’s Big Lie that the 2020 election was stolen have raised the First Amendment as a defense to sanctions and discipline for their speech and advocacy. So far, the courts to consider this defense have given it short shrift. Too short, in fact. The appropriate analysis is not to assert that attorneys lack First Amendment rights, but, rather, to recognize that those rights, while essential, are attuned to the role of the attorney in the justice system. The First Amendment should protect attorneys for Trump who filed non-frivolous suits, who refused to assist in illegal or fraudulent activities, who avoided engaging in false and misleading public advocacy or otherwise assisting in the fraud of Trump’s Big Lie. Nevertheless, Trump-supporting attorneys should find themselves bereft of a First Amendment defense—not when their views are unpopular or even wrong—but when and to the extent that they are using the state power delegated to them to practice law to thwart the justice system or undermine constitutional governance. When a government official tries to make an autocratic bid to stay in power contrary to the will of the people as determined by an election, that official is undermining our basic governmental foundation. The official should not be able to employ the aid of attorneys (who are delegates of state power derived from the people) to advise or assist in such activity. The First Amendment does not protect lawyers who use their association, advice, and advocacy to undermine our constitutional system of government from professional discipline. While a decent contingent of lawyers recognized this fact and resigned or withdrew rather than assist Trump in attempting to overturn the election, another contingent was willing to come to his aid both publicly and privately—and even advise him on how to commandeer the governmental power bestowed upon his office and the office of the Vice President to his personal ends.
Keywords: Attorney; Speech; Attorney Speech; Advocacy; Constitution; First Amendment; Public Advocacy; Trump; Big Lie; Fraud; Elections; Governance; Constitutional; Freedom of Speech; State power; Practice; Practice of Law